Energy, Exergy, Environmental and Economic Analysis of Heavy Duty Vapor Compression Chiller with Alternative Fluids in District Cooling - Sambhaji T. Kadam (AIDIC Servizi S.r.l., 2021)
A district cooling system (DCS) is superior to conventional air conditioning as it helps to reduce energy consumption and protect the environment by reducing carbon dioxide emissions. The investigation of the actual/existing vapour compression refrigeration (VCR) system used in the DCS has not been well documented. In this context, energy, exergy, environmental and economic (4E) analysis of the VCR chiller, operated with R134a, used in heavy duty existing DC plant has been systematically performed and compared with the ecofreindly refrigerant R717. The impact of the evaporation temperature on the total equivalent warming impact (TEWI), coefficient of performance, exergy efficiency and cost rate is assessed. It is observed that the COP and exergy efficiency of the VCR with R717 is around 3 % higher compared to a VCR with R134a. This is attributed to the significantly higher latent heat of evaporation, which ultimately requires a lower mass flow rate of R717. It is observed that the total global warming impact and Combined cost of R717 are lower by 1.6 % compared to the R134a. Lower TEWI is attributed to the zero global warming potential, lower compressor power and higher COP of the VCR system with R717 in comparison to R134a. However, further detailed parametric analysis considering the capital cost is required to claim the superiority of R717.